The Synergy of Blockchain and FDI: Frameworks for Advancing Cross-Border Investment Security and Efficiency - Ambrozie, Alisa-Mihaela (EuroEconomica, 2024)
This study explores the integration of blockchain technology in Foreign Direct Investment (FDI), aiming to address inefficiencies, opacity, and security challenges in traditional FDI processes. It examines blockchain’s potential to enhance cross-border investment efficiency and security through a comparative analysis with conventional FDI mechanisms. The paper proposes a strategic framework for blockchain adoption in FDI, focusing on optimizing transactional processes, fostering innovative investment models, and navigating complex regulatory environments. Key findings highlight the transformative impact of blockchain in streamlining FDI operations, enhancing transparency, and reducing costs. The framework underscores the need for technological adaptation, regulatory harmonization, and collaborative global efforts. This research contributes to the discourse on blockchain in international finance, offering insights for policymakers and stakeholders in the FDI arena. The study concludes with the recognition of blockchain’s significant potential in FDI, while acknowledging the challenges in its implementation. It calls for further research on blockchain’s evolving role in global economic structures.